2004
DOI: 10.1037/0735-7044.118.5.1111
|View full text |Cite
|
Sign up to set email alerts
|

Selective Developmental Increase in the Climbing Fiber Input to the Cerebellar Interpositus Nucleus in Rats.

Abstract: Previous studies have demonstrated that learning-related cerebellar plasticity and stimulus-elicited neuronal activity emerge ontogenetically in parallel with delay eyeblink conditioning in rats. The present study examined cerebellar interpositus field potentials and multiunit neuronal activity evoked by microstimulation of the inferior olive in Postnatal Day 17 and 24 rats. The slope and amplitude of the excitatory postsynaptic potential and the number of evoked multiunit spikes increased with age, whereas th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 45 publications
0
8
0
Order By: Relevance
“…To isolate glutamate-evoked currents, slices were bathed in normal ACSF supplemented with 200 M picrotoxin and 20 M SR95531 to block GABA A receptors and 1 M strychnine to block glycine receptors. Climbing fiber-DCN synapses are thought to be sparse at postnatal day 12 (P12) to P14 (Chan-Palay, 1977;Nicholson and Freeman, 2004). Hence, we believe that the evoked ESPCs examined in the present study were mainly mediated by mossy fibers, although we cannot rule out the possibility that a small number of climbing fiber collaterals were also activated.…”
Section: Basal Properties Of Mossy Fiber-dcn Synapsesmentioning
confidence: 64%
See 1 more Smart Citation
“…To isolate glutamate-evoked currents, slices were bathed in normal ACSF supplemented with 200 M picrotoxin and 20 M SR95531 to block GABA A receptors and 1 M strychnine to block glycine receptors. Climbing fiber-DCN synapses are thought to be sparse at postnatal day 12 (P12) to P14 (Chan-Palay, 1977;Nicholson and Freeman, 2004). Hence, we believe that the evoked ESPCs examined in the present study were mainly mediated by mossy fibers, although we cannot rule out the possibility that a small number of climbing fiber collaterals were also activated.…”
Section: Basal Properties Of Mossy Fiber-dcn Synapsesmentioning
confidence: 64%
“…First, for technical reasons, the present studies were performed using tissue derived from juvenile rats (P12-P14). Eyelid conditioning in rats has been reported to emerge at P17-P24, coincident with maturation of climbing fiber-DCN synapses (Nicholson and Freeman, 2004) and many other developmental events in cerebellum. As such, definitive statements about the relevance of mossy fiber-DCN LTD to eyelid conditioning must await confirmation in older tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Extracellular recordings in the rat interpositus suggested slight increases in the early phase of the field potential evoked by electrical stimulation of the IO in P24 vs . P17 rats (Nicholson & Freeman, ), whereas a previous study of the physiological effects of climbing fibre collateral activity on CbN cells in 3–6‐month‐old mice reported EPSCs of ∼7 pA or EPSPs of 1‐2 mV in five of 13 cells that responded to optogenetic stimulation of ChR2‐expressing afferents (Lu et al . ).…”
Section: Discussionmentioning
confidence: 99%
“…Deep cerebellar nuclei (DCN), the sole non-vestibular output from the cerebellum and an essential component of this neural circuitry, are critical to the ontogeny of eyeblink conditioned responses and have also been a target area for exploring learning-related synaptic plasticity of both excitatory (Aizenman and Linden, 2000; Pugh and Raman, 2006; Pugh and Raman, 2008) and inhibitory inputs (Bengtsson et al, 2011; Pugh and Raman, 2005; Pugh and Raman, 2008; Witter et al, 2013). Studies in developing rats have shown significant anatomical and functional changes in DCN during the first few postnatal weeks (Freeman, Jr. and Nicholson, 2000; Heinsen, 1977; Nicholson and Freeman, Jr., 2004), and thus, anatomical and functional maturation of DCN may influence the process of associative learning and memory by regulating the induction and maintenance of learning-specific changes within DCN (Freeman, Jr. et al, 1995; Freeman, Jr. and Nicholson, 2004). …”
Section: Introductionmentioning
confidence: 99%